Incidence of poor writing ability d teachers causes a low level of understanding of the English language. - Sagbay Ordoñez, Ginger Virginia (Machala : Universidad Técnica de Machala, 2015)
Este artículo trata de explicar el problema del escaso desarrollo de habilidades de escritura (escritura) hace que el maestro tiene un bajo nivel de comprensión de la información se centra en la falta de información sobre cómo los niños aprenden o adquieren el sistema de escritura, lo que sea posible la alfabetización inicial.
This article seeks to explain the problem of poor development of writing skills (writing) causes the teacher has a low level of understanding of information focuses on the lack of information about how children learn or acquire the writing system, which possible initial literacy.
Keywords: POOR SKILL; TEACHING; UNDERSTANDING; ENGLISH LANGUAGE